Prevalence and antifungal susceptibility of invasive Candida species among hospitalized patients: A cross-sectional study in Vietnam - Nguyen Thi Linh Chi; Nguyen Thi Anh Van; Le Nguyen Minh Hoa; Nguyen Minh Toan; Nguyen Thu Huong (Asian Journal of Medical Sciences, 2025)
Background: Invasive Candida infections are a major cause of illness and death in hospitalized patients. This is, especially true for that in intensive care or with serious health issues. Antifungal resistance is rising, making treatment more difficult.